Factors influencing the night market traders’ performance in Malaysia - Fauzilah, Salleh; Mazuri, Abd Ghani; Wan Kuntom, Wan Sulong; Kamariah, Yunus (2012)
This study was conducted to identify the factors affecting the night market traders’ sales performance. The factors examined were the financial resources, consumers’ tastes and preferences, product demands, business life span, and number of employees. This study tested seven hypotheses identified as the seven predictive factors influencing the performance of the night market traders’ sales. The major factors influencing the sales performance of the night market traders were found to be the number of employees and business life span. The findings of this study can be used by other researchers to conduct a comparative study in this area besides providing advisory services to traders and potential traders who wish to do business in night markets